2021
DOI: 10.1101/2021.02.26.433009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An anaphase surveillance mechanism prevents micronuclei formation from mitotic errors

Abstract: Micronuclei are a hallmark of cancer and other human disorders and have recently been implicated in chromothripsis, a series of massive genomic rearrangements that may drive tumor evolution and progression. Here we show that Aurora B kinase mediates a surveillance mechanism that integrates error correction during anaphase with spatial control of nuclear envelope reformation to protect against micronuclei formation during human cell division. Using high-resolution live-cell imaging of human cancer and non-cance… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Our data reveal that Aurora B activity is involved in the active correction of lazy kinetochores in early anaphase. This is distinct from any proposed roles of Aurora B in late anaphase 63,64 , and defines a new layer of error correction. In pre-anaphase cells, Aurora B located within the centromere-kinetochore mediates the destabilization of improper microtubule-kinetochore attachments, which are normally under low tension, rendering the kinetochores unattached 65 .…”
Section: Discussionmentioning
confidence: 67%
“…Our data reveal that Aurora B activity is involved in the active correction of lazy kinetochores in early anaphase. This is distinct from any proposed roles of Aurora B in late anaphase 63,64 , and defines a new layer of error correction. In pre-anaphase cells, Aurora B located within the centromere-kinetochore mediates the destabilization of improper microtubule-kinetochore attachments, which are normally under low tension, rendering the kinetochores unattached 65 .…”
Section: Discussionmentioning
confidence: 67%
“…However, in our live cell experiments, at the time resolution used, the kinetics of BAF and LBR recruitment to the nascent micronucleus were similar in lagging and in ensheathed chromosomes, and these were in turn comparable to NE recruitment at the main nucleus. Recent work has also countered the idea that spindle microtubules delay nuclear envelope recruitment at lagging chromosomes, in any case the NE is reformed by the end of mitosis (Orr et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we have shown that phosphorylation driven by the Aurora B gradient helps sustain kinetochore structure over the time and distance necessary for normal anaphase chromosome segregation, and regulates kinetochore disassembly as cells enter telophase. This spatial regulation of kinetochore phosphorylation may also allow kinetochore stability on lagging chromosomes to be maintained to facilitate their movement to the poles in anaphase 52 .…”
Section: Discussionmentioning
confidence: 99%